Śrīdhara Gosvāmīṅka Siddha candrikā - Śrīdhara Gosvāmī (Bijaẏa Lakṣmī Nāẏaka, 1980)
Sacred work of the Mahima dharma, Hindu religious movement, founded by Mahimā Gosāim̐, d. 1876; supposedly written by a Brahman before the founding of the sect